Multiwall carbon nanotubes based triboelectric nanogenerators - Ani, Mohd Hanafi; Zulkeflee, Muhammad Zakhuan; Kaderi, Akbar; Sutjipto, Agus Geter Edy; Salim, Nurjannah (Trans Tech Publications Ltd, 2022)
Nanogenerators are a tiny device that can harvest small-scale ambient energies. Carbon nanotubes (CNTs) have been integrated into the device to boost the performance and increasing the efficiency of harvested electrical energy. Multiwall carbon nanotubes (MWCNT) have lower electrical properties compared to single wall carbon nanotubes (SWCNT). However, single wall carbon nanotube is difficult to grow in mass scale and subject to higher production cost. This paper aims to use MWCNT as an active material in triboelectric nanogenerator. The samples were prepared by spin coating of MWCNT on ITO glass at various concentrations. XRD result shows that MWCNT mainly present at crystal planes of (0 0 2), (1 0 0) and (0 0 4). The device has produced maximum current density of 165 μAm-2, and power density of 1,289 μWm-2. Apparently, the concentration of MWCNT in the solution to fabricate the device plays critical roles on the current output of the device. The application of multiwall carbon nanotube based triboelectric nanogenerator is promising for low cost self-powered nanogenerators.